The Effect of Orlistat Administration in Change of Glycemic Control and Weight Loss of Obesity or Overweight Patients with Type 2 Diabetes Mellitus - Johan, Abu Rizal Dwikatmono; Dewanti, Linda; Putri, Anandia Nafisah; Pantoro, Benny Iswanto; Albab, Chabib Fachry; Hutauruk, Maria Marind Desrianti; Novitasari, Triana (Folia Medica Indonesiana, 2022)
Hightlight: • The effect of orlistat on glycemic control and weight loss in overweight or obese type 2 diabetes mellitus patients was determined • HbA1c and FPG level in overweight and obese type 2 diabetes mellitus patient can improved by orlistat as an adjuvant therapy. Abstract: Risk of Type 2 diabetes mellitus (T2DM) increases steadily with increasing overweight and obesity, and these two-health problems are emerging epidemics worldwide. Orlistat, a lipase inhibitor for weight loss drug, is often used in T2DM medication as adjuvant therapy, but effectiveness of the drug for improving glycemic control on T2DM patients is unclear. This study was to determine the effect of orlistat on glycemic control and weight loss in overweight or obese patients with T2DM. Term "Orlistat” AND "(obesity OR overweight)” AND "(HbA1c OR A1C)” AND "diabetes” were systematically searched in Pubmed and Science Direct web databases up to March 2021. Only randomized controlled study (RCT) methods studies were included in this study. Collected final samples were presented in a table with narrative review. There were 9 RCT studies with a total 2,175 subjects that met inclusion criteria. Of the sample, 360 mg/day orlistat as an adjuvant therapy, was administered to overweight or obese T2DM patients together with hypocaloric intake (8 studies) or without hypocaloric intake (1 study) intervention. They were examined for 12-52 weeks. From 2 short-term (12 weeks) studies, one study revealed that orlistat improved HbA1c and fasting plasma glucose (FPG) level significantly, while one study showed no significant effect compared to placebo. Seven other studies (long term observation) had found that orlistat significantly improved HbA1c and FPG level. All studies found that orlistat significantly reduced body weight. As an adjuvant therapy, Orlistat improved HbA1c and FPG level in overweight and obese T2DM patients.